EFFECT OF DIFFERENT SOIL TYPES AND SHADE LEVELS ON GENERATIVE GROWTH Asystasia gangetica (L) subsp. Micrantha ON SECOND SHOOTING - H., Nursyafi’i,; Kusumawati, N. C.; Witariadi, N. M. (Jurnal Peternakan Tropika; Vol 12 No 5 (2024): Vol. 12 No. 5 Tahun 2024; September - October, 2024)
Alternatives to the development of green food may take place on a plantation or under a shade.  Research aims to identify the different kinds of soil and shade effects on the generative growth of Asystasia gangetica (L.) subsp. Micrantha on second cut. The study carried out in the Village of Sading, Mengwi District, Badung District, ran from April-June 2023. The design used was a complete random design (RAL) a two-factor split plot. The main plot ( main plot ) is the land type: TM: Mediterranean Land; TL: Soil of Latosol; and TR: Land of Regosol. Tenders ( sub plot ) are the swine shade N1: shade 20%; N2: 40% shade; and N3:60% shade. From the treatment there ware 9 combinations of treatment, and each treatment is repeated 3 times and thus obtained 27 experimental units. The observed variable is the first-time flowering, the amount of inflorescence, the amount of flowers, the amount of pods, the amount of seeds, and the weight of the seeds. Research shows no interaction between soil types and different shade levels of Asystasia gangetica (L.) subsp. Micrantha on the second count. Treatment of soil does not affect generative growth in all variables, but it tends to be higher on regosol soil (TR). Treatment of shade levels affects the generic growth of flowering time first in all variables, the highest yield is shown at 20%, and the shade level of 40%-60% can suppress generic growth.  It may be concluded that there is no interaction of different types of soil and a different level of shade for the generative growth of Asystasia gangetica (L.) subsp. Micrantha on second cut. This type of soil does not affect the generative growth of Asstasia gangetica (L.) subsp. Micrantha at a second cutting, but regosol land types tend to provide the best generic growth. 20% of shade gives generative Asystasia gangetica (L.) subsp micrantha the best on a second cut, while a 40%- 60% can offset generative Asystasia gangetica (L.) subsp. Michrantha on the second cut.